Electronic learning course as a means of the development of spheres of individuality of a student of higher educational institution (on the example of the discipline "Foreign language") - Paniushkina, Marina Aleksandrovna; Ponikarovskaya, Valentina Viktorovna; Matsakova, Natalia Vladimirovna; Volkova, Irina Sergeevna (Razvitie obrazovaniâ (Online), 2025)
This work is devoted to the development of the spheres of individuality of a university student through the integration of an electronic course into the educational process during foreign language classes for the first- and second-year bachelor students of Immanuel Kant Baltic Federal University. The creation of a specially designed course in the electronic information and educational environment (https://eios.kantiana.ru/) is based on a number of principles: individualization and variability of the studying process, practical focus of the educational material. The electronic learning course allows the student to develop spheres of individuality through planning and building an educational route, through the choice of educational material, preparation of creative project works, through monitoring academic progress, and etc. Experimental verification of the exposed hypothesis that the development of the student’s individuality spheres will be quite effective provided that a specially created electronic learning course is implemented into the educational process, allowing to activate all student’s mental processes when studying a foreign language. This verification is realized in accordance with three stages. The obtained results have confirmed the proposed hypothesis about a positive influence of the electronic learning course on the development of spheres of individuality of a student in the process of studying.